2018
DOI: 10.1016/j.ejvs.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose Reduction During EVAR: Results from a Prospective Multicentre Study (The REVAR Study)

Abstract: With adherence to the ALARA principle and routine application of fusion imaging guidance for EVAR, low radiation exposure compared with the published literature can be achieved in a real world setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 24 publications
(18 reference statements)
0
23
0
Order By: Relevance
“…If utilization of lead glasses had also been neglected, the annual equivalent dose limit for the eyes would have been reached with just one PAE procedure per week. Taken together, all these data emphasize the need for careful and systematic application of the ALARA principle in the clinical context of PAE; strict adherence to the ALARA concept in other complex endovascular procedures has resulted in dramatic reduction of radiation exposure (Hertault et al 2018). In selected patients, the herein proposed reduction of steep oblique views during PAE appears to be a feasible step towards the implementation of this principle.…”
Section: Discussionmentioning
confidence: 75%
“…If utilization of lead glasses had also been neglected, the annual equivalent dose limit for the eyes would have been reached with just one PAE procedure per week. Taken together, all these data emphasize the need for careful and systematic application of the ALARA principle in the clinical context of PAE; strict adherence to the ALARA concept in other complex endovascular procedures has resulted in dramatic reduction of radiation exposure (Hertault et al 2018). In selected patients, the herein proposed reduction of steep oblique views during PAE appears to be a feasible step towards the implementation of this principle.…”
Section: Discussionmentioning
confidence: 75%
“…Recent studies concluded that the number of prostatic arteries origins and anastomoses that could be identi ed were signi cantly higher with CBCT than with DSA [11], and that CBCT provided essential information that was not available with DSA in 46% [12] to 60.8% [11] of patients. Finally, advanced imaging techniques such as 3D road-mapping should be utilized as they can contribute to both performing safer and more e cient procedures, and reducing x-ray dose and procedure time [33,34].…”
Section: Imaging Optionsmentioning
confidence: 99%
“…The 'technological/managerial/engineering route' involves any technology-based interventions and managerial decisions regarding safety that take place at higher levels of the organization. Examples include perfecting radiation safety equipment to reduce radiation doses [4][5][6][7][8][9][10][11] and developing and implementing standard operating procedures to routinely measure (occupational) radiation doses and manage overexposed patients or team members.…”
Section: 1mentioning
confidence: 99%